Body-on-a-Chip Systems for Animal-free Toxicity Testing. Issue 5 (October 2016) - Mahler, Gretchen J.; Esch, Mandy B.; Stokol, Tracy; Hickman, James J.; Shuler, Michael L.
Body-on-a-chip systems replicate the size relationships of organs, blood distribution and blood flow, in accordance with human physiology. When operated with tissues derived from human cell sources, these systems are capable of simulating human metabolism, including the conversion of a pro-drug to its effective metabolite, as well as its subsequent therapeutic actions and toxic side-effects. The system also permits the measurement of human tissue electrical and mechanical reactions, which provide a measure of functional response. Since these devices can be operated with human tissue samples or with in vitro tissues derived from induced pluripotent stem cells (iPS), they can play a significant role in determining the success of new pharmaceuticals, without resorting to the use of animals. By providing a platform for testing in the context of human metabolism, as opposed to animal models, the systems have the potential to eliminate the use of animals in preclinical trials. This article will review progress made and work achieved as a direct result of the 2015 Lush Science Prize in support of animal-free testing.